Proposed Maintenance Plan for Maker Machinery with Reliability Centered Maintenance (RCM) Method and Maintenance Value Stream Mapping (MVSM) at PT. XYZ - Vidya, Aditya; Aidil, Joumil (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT XYZ is a company engaged in cigarette production, where most of the production process uses automatic machines. The problem faced by the company is damage that occurs at any time before the scheduled maintenance interval causes overhaul and replacement or corrective maintenance activities which causes downtime and stops the production process on production machines that have a high average downtime compared to other machines. With these problems, calculations are carried out to obtain maintenance scheduling time intervals. The index of fit is used to measure how well the Weilbull distribution is based on the time to repair data. The fit index value (r) for the Hoper component downtime data is 0.92 or 92%, which means that the Hoper component downtime data can be completed using the Weilbull distribution. Calculation of the time to failure and time to repair parameters uses the Weilbull distribution by finding the intercept (a), gradient (b), shape parameter (α) and scale parameter (β). Calculation of the mean time to failure and mean time to repair using the results of parameter calculations using the Weilbull distribution based on the gamma table results in a mean time to failure of 1054.67 hours and a mean time to repair of 218.18 minutes. Calculation of the inspection time interval on the Hope component for 250 hours or 10 days per month. Analysis of maintenance efficiency using the maintenance value stream mapping approach obtained a maintenance efficiency percentage of 77.5%. Activities that provide added value have a longer time, namely 218.18 minutes. While activities that do not have added value is 63.2 minutes.